Applying digital technology to promote active and healthy confinement lifestyle during pandemics in the elderly - Ammar, Achraf; Bouaziz, Bassem; Trabelsi, Khaled; Glenn, Jordan; Zmijewski, Piotr; Müller, Patrick; Chtourou, Hamdi; Jmaiel, Mohamed; Chamari, Karim; Driss, Tarak; Hökelmann, Anita (Biology of Sport, 2021)
Although recognized as effective measures to curb the spread of the COVID19 outbreak, social distancing and home confinement have generated a mental health burden with older adults who are considered to be more vulnerable to psychosocial strains. To date, the application of digital technologies in response to COVID-19 pandemic has been narrowed to public-health needs related to containment and mitigation. However, information and communications technology (ICT)-based initiatives directed toward prediction and prevention of psychosocial support are still limited. Given the power of digital health solutions to allow easy and accurate characterization and intervention for health and disease, as well as to flatten the COVID19 incidence curves in many countries, our ECLB-COVID19 consortium is highlighting the importance of providing innovative ICT-based solutions (ICT-COVID-Companion) to improve elderly physical and mental health, thereby preventing/dampening psychosocial strain during pandemics. Based on innovative approaches (e.g., emotional/social computing, open social platform, interactive coaching, gamification, fitness-tracker, internet of things) and smart digital solutions (smartwatch/smartphone), smart companions must provide safe personalised physical, mental and psychosocial health surveillance. Additionally, by delivering personalised multi-dimension crisis-oriented health recommendations, such innovative crisis-oriented solutions would help (i) facilitate a user’s adherence to active and healthy confinement lifestyle (AHCL), (ii) achieve a rapid psychosocial recovery in case of depression issues and (iii) enhance preparedness for eventual future pandemics.